2020
DOI: 10.3390/genes11010068
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome Analysis Reveals Potential Regulatory Genes Related to Heat Tolerance in Holstein Dairy Cattle

Abstract: Heat stress affects the physiology and production performance of Chinese Holstein dairy cows. As such, the selection of heat tolerance in cows and elucidating its underlying mechanisms are vital to the dairy industry. This study aimed to investigate the heat tolerance associated genes and molecular mechanisms in Chinese Holstein dairy cows using a high-throughput sequencing approach and bioinformatics analysis. Heat-induced physiological indicators and milk yield changes were assessed to determine heat toleran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(24 citation statements)
references
References 52 publications
1
22
0
1
Order By: Relevance
“…In the study, the N50 length of unigenes was 1825 bp, indicating that the sequence assembly was high in quality and suitable for intensive research. Moreover, the N50 could be compared with those of other species [46][47][48]. The average length of the unigenes was larger (1050 bp) (Table 2), than those in previous studies, such as those of Myrica rubra (531 bp) [49] and Sorbus pohuashanensis (770 bp) [50].…”
Section: Discussionmentioning
confidence: 89%
“…In the study, the N50 length of unigenes was 1825 bp, indicating that the sequence assembly was high in quality and suitable for intensive research. Moreover, the N50 could be compared with those of other species [46][47][48]. The average length of the unigenes was larger (1050 bp) (Table 2), than those in previous studies, such as those of Myrica rubra (531 bp) [49] and Sorbus pohuashanensis (770 bp) [50].…”
Section: Discussionmentioning
confidence: 89%
“…Srikanth et al reported that genes and signaling pathways for innate immunity were altered in PBMCs in heat-stressed Holstein calves [ 37 ]. In addition, Liu et al conducted transcriptome analysis for whole blood to find potential regulatory genes related to heat tolerance in Holstein cows [ 38 ]. They selected heat-tolerant and non-heat-tolerant Holstein cows based on heat-stress scoring parameters such as rectal temperature, respiration rate, and milk yield change, then compared the gene expressions in blood immune cells between heat-tolerant and non-heat-tolerant cows.…”
Section: Discussionmentioning
confidence: 99%
“…Whole transcriptome analysis was used by many researchers to explore various fields of animal genetics ( 78 ). Liu et al ( 79 ) explored the genes associated with heat tolerance and the molecular mechanisms adopted by Chinese Holstein dairy cows through transcriptomic analysis. They reported nearly 200 differentially expressed genes (DEGs) in heat-stressed cattle when compared to their control.…”
Section: Genomic Applications For Identifying Superior Dairy Cows Bestmentioning
confidence: 99%